The Role of the British Royal Family's Digital Diplomacy - Miková, Linda; Peterková, Jana, 1971-; Trávníčková, Zuzana, 1977-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis explores how the British Royal Family uses social media as a tool of digital diplomacy to project soft power in the 21st century. Focusing on official Instagram and X (Twitter) accounts in 2024, it explores the communication strategies of King Charles III and Queen Camilla with those of the Prince and Princess of Wales. Through content and discourse analysis, the research identifies key themes, rhetorical strategies, and patterns of engagement, guided by Nye’s concept of soft power and Cull’s framework of public diplomacy. The findings reveal that while the King and Queen emphasize tradition, ceremonial function, and institutional continuity, the Prince and Princess adopt a more personal, emotionally resonant tone that fosters stronger public engagement and relatability. The analysis also shows that the Royal Family subtly promotes political values and cultural identity, acting as a symbolic, apolitical representative of the UK on the global stage. Despite lacking formal policy power, their digital presence contributes to the UK's international image and legitimacy. This thesis concludes that soft power in the digital era increasingly depends on narrative construction, emotional appeal, and personal credibility, rather than institutional authority. The study contributes to emerging research on symbolic actors in digital diplomacy and the evolving nature of public engagement in soft power projection.
Vedoucí práce: Jana Peterková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses